ANALISIS GAYA BELAJAR MAHASISWA PADA MATA KULIAH GEOLOGI DALAM PEMBELAJARAN BERBASIS SPATIAL PROBLEM BASED LEARNING (SPBL) DENGAN PENDEKATAN OPTIC-SCRAP - Anisah, Reni; Bekti Susetyo, Bigharta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to identify and describe the learning style tendencies of Geography Education students in the Geology course during Spatial Problem Based Learning (SPBL) with the OPTIC-SCRAP approach. The research method used is descriptive quantitative. The research sample consists of 29 undergraduate Geography Education students from the 2025 cohort, selected through purposive sampling techniques based on a spatial literacy preliminary test. Data were collected using a learning style questionnaire instrument with a Likert scale that has been tested for validity and reliability, then analyzed using descriptive statistical techniques. The results showed that student learning style tendencies were dominated by the auditory type at 35.86% with an average score of 84.03, followed by the visual type at 35.57% with an average score of 83.34, and the kinesthetic type at 28.57% with an average score of 66.93. Based on gender, male students showed a dominance in the auditory learning style at 36.46%, while female students were slightly more dominant in the visual learning style at 35.66%. Viewed from academic background, both Science (IPA) and Social Studies (IPS) graduates consistently showed dominance in the auditory learning style, at 36.36% for IPA and 35.75% for IPS, respectively. Overall, this research concludes that the OPTIC-SCRAP approach is very effective for students with visual and auditory learning style tendencies, because the image analysis steps and systematic discussions within it facilitate optimal information processing. However, the low proportion of kinesthetic learning styles indicates the need for strategy modifications, such as the integration of manipulative activities or more intensive field simulations, so that this approach remains inclusive and capable of providing equal learning outcomes for all learner profiles.